Could neutrophil/lymphocyte ratio be an indicator of coronary artery disease, coronary artery ectasia and coronary slow flow? - Yilmaz, Mucahid; Korkmaz, Hasan; Bilen, Mehmet Nail; Uku, Okkes; Kurtoglu, Ertugrul (Sage Publications Ltd, 2016)
Objective: To determine whether neutrophil/lymphocyte ratio (NLR) differed between patients with isolated coronary artery disease (CAD), isolated coronary artery ectasia (CAE), coronary slow flow and normal coronary anatomy. Methods: Patients who underwent coronary angiography were consecutively enrolled into one of four groups: CAD, coronary slow flow, CAE and normal coronary anatomy. Results: The CAD (n = 40), coronary slow flow (n = 40), and CAE (n = 40) groups had similar NLRs (2.51 +/- 0.7, 2.40 +/- 0.8, 2.6 +/- 0.6, respectively) that were significantly higher than patients with normal coronary anatomy (n = 40; NLR, 1.73 +/- 0.7). Receiver operating characteristics demonstrated that with NLR > 2.12, specificity in predicting isolated CAD was 85% and sensitivity was 75%, with NLR > 2.22 specificity in predicting isolated CAE was 86% and sensitivity was 75%. With NLR > 1.92, specificity in predicting coronary slow flow was 89% and sensitivity was 75%. Multivariate logistic regression analyses identified NLR as an independent predictor of isolated CAE (beta = -0.499, 95% CI -0.502, -0.178; P < 0.001), CAD (beta = -0.426, 95% CI -1.321, -0.408; P < 0.001), and coronary slow flow (beta = -0.430, 95% CI -0.811, -0.240; P = 0.001 Table 2). Conclusions: NLR was higher in patients with CAD, coronary slow flow and CAE versus normal coronary anatomy. NLR may be an indicator of CAD, CAE and coronary slow flow.
Keywords: Coronary artery disease; coronary artery ectasia; coronary slow flow; neutrophil/lymphocyte ratio